An Evaluation of Serum and Salivary Adipokines (Leptin and Resistin) Levels in Periodontal Health and Disease - Talib A Karam; Khulood A Al-Safi (College of Dentistry/ University of Baghdad, 2015)
Background: With the start of the current century, increased the interest in the role of the adipose tissue derived substances that named adipokines in the inflammatory diseases of the human being including the inflammatory periodontal disease, but scientific evidences were not clearly demonstrate the association between these adipokines and periodontal pathologies. Materials and Methods: Forty two subjects male only with normal body mass index were selected for the study with an age ranged (30-39 years). Samples were divided into three groups of 14 subjects in each group based on clinical periodontal parameters; clinically healthy gingiva (group I), gingivitis group (group II) and chronic periodontitis patients group (group III), from whom saliva and serum samples were collected for estimating the levels of leptin and resistin using Enzyme-Linked Immuno Sorbent Assay (ELISA). Results: The results showed that the serum level of leptin and resistin were significantly higher in chronic periodontitis patient (9.81 ng/ml, 6.55 ng/ml) respectively as compared to gingivitis and healthy control groups (leptin; 8.10 ng/ml, ng/ml, resistin; 5.85 ng/ml, 5.45 ng/ml) respectively. On the other hand the level of leptin in saliva of patients with chronic periodontitis (0.17 ng/ml) was significantly lower than that of its salivary levels in gingivitis and healthy control groups (0.21 ng/ml, 0.29 ng/ml) respectively. Whereas, salivary resistin levels was significantly higher in chronic periodontitis patient(14.45 ng/ml) when compared to the gingivitis group (11.59 ng/ml) and the health control group (6.43 ng/ml). Conclusions: Concomitant raise in serum leptin, serum resistin and salivary resistin, while a sensible reduction in salivary leptin with conversion from periodontal health state to periodontal disease state. These finding may draw a suggestion on the role of leptin and resistin in the relation between periodontal disease and the systemic health since the increase in their level were associated with a various systemic pathologies.